International Capital Markets : Recent Developments and Short-Term Prospects - Williams, R. (Occasional Papers; Occasional Paper ;, 1980)
This publication begins a new series, Occassional papers, designed to fill a gap in the range of publications of the IMF. Occasional Papers will not be on a particular theme but will contain studies on a variety of economic and financial subjects of importance to the work of the Fund, such as overall developments in national economies, the behavior of international capital markets, and problems related to the functioning of the international monetary system.